Dosimetry characteristics of ultra-high dose rate X-ray: a short review - Luyan Tao; Song Feng; Yiwei Yang; Bo Zheng (Frontiers in Physics)
FLASH radiotherapy (FLASH-RT) has emerged as a significant area of research in the field of radiotherapy in recent years. This innovative technology delivers ultra-high dose rate radiation in a very short time, effectively damaging tumor cells while minimizing the impact on surrounding normal tissues. Currently, the beams that have been proven to achieve the FLASH effect include electrons, protons, and photons. X-ray FLASH-RT exhibits enhanced penetration capabilities and superior cost-effectiveness. However, the detectors currently used for X-ray FLASH-RT dose rate measurement generally exhibit saturation effects and a limited dose linear response range. In this review, we provide a comprehensive summary of the primary devices used to generate ultra-high dose rate X-rays. Additionally, we classify and describe the reported detectors for monitoring the high-dose rate in X-ray FLASH-RT according to three main types: gaseous detectors, scintillators, and semiconductors. This offers researchers valuable insights and a solid reference for selecting and optimizing detectors to achieve more precise and reliable high-dose rate X-ray measurements in X-ray FLASH-RT. Additionally, it provides significant support for the further development and clinical implementation of FLASH-RT technology.